Investigating Fatigue in Offshore Drilling Workers: A Qualitative Data Analysis of Interviews. Issue 1 (2nd January 2019) - Mehta, Ranjana K.; Smith, Alec; Williams, Jason P.; Camille Peres, S.; Sasangohar, Farzan
OCCUPATIONAL APPLICATIONS: Interviews were conducted with offshore operators in the oil and gas industry in order to gain insight into their experiences of fatigue and associated mitigation strategies. These interviews indicated that effective mitigation methods and techniques originate from both the organization and the worker. Current industry practices and potential recommendations to manage worker fatigue in the oil and gas operations are provided. These practices and recommendations include improving sleep quality through effective sleep-cabin arrangements, reducing physical and cognitive workload through improved work/tool/environment designs, and facilitating periodic fatigue monitoring. TECHNICAL ABSTRACT Background: Offshore drilling in the oil and gas industry presents a fast-paced, hazardous work environment that can evoke states of fatigue or tiredness. Purpose: To gain insight into the day-to-day experience and mitigation of fatigue among workers in this industry. Methods: Interviews were conducted with eleven offshore personnel working on an offshore rig in the Gulf of Mexico. Qualitative data analysis of interview transcripts provided an initial code set for categorizing the data. Results: The coding process, enhanced using visualizations, revealed some themes that highlighted dimensions of fatigue, such as physical and cognitive aspects, in addition to the more commonly recognized source of fatigue, namely shiftwork. These themes also emphasized potential fatigue mitigation strategies that were either organizationally or individually driven. Such strategies include needs for improved coordination around shift work schedules and sleeping arrangements, and a widespread perceived obligation to work past fatigue, despite being encouraged to report symptoms. Conclusions: These results provided a better understanding of worker perceptions of fatigue sources, reporting challenges, and adoption of personal mitigation strategies among oil and gas workers. These results can also inform specific organizational opportunities for mitigating fatigue in offshore drilling operations. Potential strategies that encourage periodic fatigue monitoring, improve sleep quality, and reduce work-related physical and cognitive overload should be examined for effective adoption in this industry.